The Mediating Effects of Organizational Justice in Determining the Relationship between Performance-Based Pay and Employees’ Turnover Intention - Kuan, Mei Yang; Rusli, Ahmad; Siti Mariam, Abdullah (Faculty of Cognitive Sciences and Human Development (FCSHD), UNIMAS, 2015)
This is a study on employees’ perception of justice towards performance-based pay and the effect of these perceptions on their turnover intention. This study aims to examine the mediating role played by distributive and procedural justice in linking pay distribution and pay procedure of performance-based pay to employees’ turnover intention. A review of past literature in this particular area has prompted the researchers to narrow the gaps in previous studies. Towards that, this study utilized questionnaires which were administered among 50 non-managerial employees currently working in a private company located in Kuching, Sarawak, East Malaysia. Data analysis was done using Statistical Package for Social Sciences (SPSS), Version 20.0. Pearson Correlation and Stepwise Regression were used to examine the relationship between the variables. The outcomes of Stepwise Regression revealed that distributive justice fully mediated the relationship between pay distribution and employees’ turnover intention in contrast to procedural justice which did not have a significant impact in the relationship. The findings of this study are useful references for organisation management of the pay system to improve employees’ performance.